Aging and Positive Psychology - Marks, Ray (Journal of Aging Research And Healthcare, 2021)
Background Aging, a state often associated with poor emotional health status greatly impedes life quality and independence for many. Aim This mini review examines the potential of the concept of positive psychology as an active approach to fostering successful or more successful, rather than suboptimal aging. Methods and Procedures Articles that addressed the current topic of interest and were located in the PUBMED, Medline, Web of Science, PsycINFO and Google Scholar electronic data bases were carefully sought and analyzed and presented in narrative form. Results Various forms of positive psychology appear to provide a safe efficacious evidence based approach for purposes of ameliorating various degrees of anxiety and depression and for improving cognition, life quality, and health well-being in diverse subgroups of older adults Conclusion More research to examine who might benefit most from this highly promising form of intervention, and in what respect appears to have considerable merit in light of the growing populations of older adults and few intervention options to help them to age optimally and as successfully as possible.
Keywords: Anxiety; Cognition; Depression; Positive Psychology; Successful Aging